Sociale controle, misdaad en het geweldsmonopolie. De veranderende rol van de politie - Spierenburg, P. (BMGN - Low Countries Historical Review, 2008)
Social Control, Crime and the Monopoly on the Use of Force. The Changing Role of the Police This review article identifies three major developments within the history of the police force in Europe: 1. the spread of the police force and their politicolegal organization; 2. the transition from a multi-functional institution providing various services and fostering a traditional mentality to a professional apparatus focused on crime prevention; 3. changes in the relationship between the police and the state’s monopoly on the use of force, eventually leading to a more restrained and politically neutral form of maintaining law and order. De geschiedenis van de Nederlandse politie deals disproportionately with the first aspect. Within the second field, there is little attention for the mentality and additional tasks of nineteenth century policemen, but sufficient attention for the differentiation in police work in the twentieth century. With respect to item 3, the focus is overwhelmingly on the suppression of social protests. The relationship between the police and the people, in particular the ‘charming offensive’ during the 1970s, remains largely unexplored. This review is part of the discussion forum ’De geschiedenis van de Nederlandse politie’ (Cyrille Fijnaut).